Behavior of Hybrid CFRP Laminated Thin-Walled Beams: Experimental, Numerical, and Analytical Evaluations - A. M. Yosri; Gouda M. Ghanem; Mohamed A. E. Salama; Majed Alzara; Mohamed A. Farouk; MD Alhaz Uddin; Mohamed AbdelMongy; A. Ehab (Advances in Civil Engineering)
The aim of this paper is to assess the structural behavior of hybrid thin-walled beams which were fabricated using laminated carbon fiber reinforced polymer (CFRP). Seven hybrid (CFRP) I-beams were fabricated, instrumented, then have been tested under monotonic four-point loading in order to evaluate their behavior up to failure. In constructing the I-beam specimens which were evaluated in this study, plywood core was implemented on both the web and flanges. Several important parameters were conducted in this study considering changing both of the ply orientations and stacking sequences of laminated fibers, also changing the shear span-to-depth ratio (a/d) of the specimens. The experimental results showed that stacking sequence is the most significant parameter that influences both flexural strength and stiffness of the hybrid beams. Also, the experimental results promoted the effectiveness of the core material for enhancing the flexure (bending) stiffness of beams. Then, these results were compared with a previous simulated study which used the finite element modeling to model the beams. Also, in order to evaluate the efficiency of the CRFP beams, the results were compared to similar steel beams having the same dimensions of the CFRP beams. As compared to steel beams, the load carrying capacity of the laminated beams is being high compared with steel beams when taking into consideration their specific strength ratio.